Bombus (Pyrobombus) jonellus (Kirby, 1802) in the north-western Russian Plain: its distribution and ecology - Potapov, GS; Kolosova, YuS (Arctic Environmental Research, 2020)
The fauna and ecology of bumblebees in the European North are quite well-studied. However, there is a scarcity of information about the distribution and ecology of certain species of bumblebees, especially for the territory of Northern Russia. In this study, we summarised materials concerning Bombus (Pyrobombus) jonellus (Kirby, 1802), which is typical bumblebee species for the north-western portion of the Russian Plain and surrounding areas. The studied territory includes the Arkhangelsk Region and the western part of the Nenets Autonomous District, i.e. a wide strip from taiga to tundra ecosystems. Due to the studies of materials that were collected over a period 17 years, we established that B. jonellus is widely distributed and the northern border of its range within the studied region reaches the northern part of the Kanin Peninsula. In the north-western Russian Plain, B. jonellus has been found in various types of habitats, the most common being coniferous and birch forests, secondary meadows and ruderal patches. In the Solovetsky Islands, White Sea, Russia, B. jonellus is typical on coastal heathlands. In the northern part of the studied region, B. jonellus has a tendency to forage in open habitats and visits a wide range of entomophilous plants, mostly of the family Ericaceae. Our findings highlight that the territory of the north-western Russian Plain and surrounding areas is where B. jonellus is widely distributed and abundant, being recorded in different types of habitats.